Caracterização genética dos vírus Dengue sorotipo 1 isolados em Roraima durante os anos de 2008 a 2010 - Sousa, Débora Dinelly de (2013)
In northern Brazil, Roraima is highlighted as one of the dengue virus hyperendemic states, where the four serotypes has been circulating for the last three years and with a high incidence of this disease in the last decade. On the other hand, its geographic localization has an important part on the entry of new genotypes/serotypes of dengue in Brazil. DENV-1, after a short incursion in the state in years 1981 and 1982, was reintroduced in 2000 and it was one of most isolated serotypes until 2011. Nevertheless, there is little data that shows the occurrence of genetic variability or any evolution in genetic composition from this serotype on infections occurred in different years. The objective of this project was to perform a molecular characterization of the envelope gene isolated from DENV-1 on infections occurred between 2008 and 2010 in Roraima. The samples were inoculated in C6/36 cells from Aedes albopictus, and identified by indirect immunofluorescence and RT-Hemi-Nested-PCR techniques. To obtain an amplicom from the envelope region, it was made an RT-PCR test with specific primers, generating a product with 1724 bp. The amplicons were sequenced and the consensus sequences were obtained using the program Geneious V.5.5.4. For molecular analysis, the current sequences were compared to sequences from the four serotypes of dengue virus and also compared to five genotypes of DENV-1 from different parts of the world available on GenBank. The phylogenetic reconstruction was made by two methods, Maximum-likelihood and Bayesian. All of the isolates were grouped in genotype V of DENV-1. The sequences showed 99-100% of similarity with strains of DENV-1 from neighbor countries and states as the Bolivarian Republic of Venezuela, Guyana, Colombia and Amazonas, they were grouped on a phylogenetic tree forming a subclade with strains of these countries and Caribbean region, and besides indicating, once more, Roraima as a possible entry route of serotypes/genotypes of dengue in Brazil, fact totally proven in 2010 with the entry and dispersion of genotypes II of DENV-4. The Brazilian strains of genotype V of DENV-1 formed three distinct lineages. The isolates of this study (2008-2010) were grouped in lineage III, different from the strain that circulated in the state in 2001, which belonged to lineage II. When these sequences were compared, it was found four aminoacid substitutions, two of them (E428 e E436) probably neutral which did not change tridimensional conformation of the envelope, since amino acids with similar physicochemical characteristics were changed (Leucine x Valine; Isoleucine x Valine), and two substitutions (E227 e E338) with high probability of changing the envelope (Proline x Serine; Leucine x Serine). These results may indicate an adaptive evolution of DENV-1 or the entry of a new lineage in the State, emphasizing the importance of molecular monitoring strains of DENV in circulation in certain regions, allowing better understanding of the virus.